Internalization of Religious Values Using the Argument-Driven Inquiry Model to Improve Critical Thinking Skills during the COVID-19 Pandemic - Fitriani, Yeyen Siti; Juanda, Anda; Roviati, Evi (Biosfer: Jurnal Tadris Biologi, 2020)
This research aimed to describe students’ activities, the improvement differences of students' critical thinking skills, and explain students' responses toward the internalization of religious values using the Argument-Driven Inquiry model on reproductive system material at eleventh-grade students of MAN 1 Kuningan. The method used in this research was the quantitative method with the experimental pretest-posttest control group design. This research population was all eleventh-grade students of MAN 1 Kuningan, which consisted of eight classes, five science classes, and three social studies classes. The research sample was taken using a random sampling technique. This research sample was class XI IPA 1 as the experimental class (35 students) and XI IPA 3 as the control class (34 students). The data collection techniques employed were observation, tests, and questionnaires. The data was analyzed using SPSS v.25 software. The results obtained showed that the highest learning activity was at the data collection stage. There was an improvement in students’ critical thinking skills in the experimental class and the control class. The average N-Gain of the experimental class was 0.69, and the control class was 0.33. The sig statistical test results were 0.000 <0.655, meaning that H0 was rejected and Ha was accepted. Thus, there was a significant improvement in students' critical thinking skills between the experimental and control classes.